The role of sensous flow and sensing the ground in movement skill experiences—a reflection using the practice of yoga as an example - Engelsrud, Gunn Helene (Frontiers in Sports and Active Living, 2023)
This contribution takes a phenomenological approach to explore the sensuous flow and perceived experiences in practicing movement skills, using the practice of yoga as a case study. The article focuses on the role of perception and the anonymous aspect of the body's responses in practicing skills and capabilities to move, with yoga as an example. The author uses a phenomenological framework, highlighting how passivity and sensuous flow is available in the practice of yoga. Edmund Husserl's concepts of passive synthesis and Thomas Fuch & Sabine Koch interpretation of bodily resonance and Kym Maclaren's “letting be” are used as analytic frames to illuminate how movement experiences are dependent on bodily awareness towards the ground, without demanding conscious willpower or focus on force, but listening and sensing with and from the body. The article aims to illuminate the ambiguous character of how movement experienced from a first-person perspective gains importance by understanding oneself, others, and the world as reciprocal and intertwined phenomena.